Metodologi dan Historiografi Indonesia: Tantangan Indonesiasentrisme dalam Era Global - Ardhana, I Ketut; Puspitasari, Ni Wayan Radita Novi (Jurnal Sejarah Indonesia, 2024)
The Indonesian centrism that was introduced after the formation of the modern Indonesian state experienced various interpretations in the dynamics of historical debate in Indonesia. This historical interpretation arises in connection with, on the one hand, the opinion that Indonesiacentrism is centered on Indonesia's interests, and on the other hand, it is thought to give rise to a lack of awareness of the development of historiography in other regions, both in local and regional contexts. Questions arise, including: first, how to interpret the understanding of Indonesian centrism in the context of historiography in global dynamics. Second, why does controversy arise between these interpretations, which seem to contrast one with the other? Third, how to position the understanding of Indonesian centrism in the context of the development of historiography, which is capable of developing not only local and national history studies but also regional history studies? In discussing this issue, efforts will be made to gain a better understanding of Indonesian historiography, which can strengthen Indonesianness itself without reducing the presence of dynamics in the local area and other regional areas.